2022
DOI: 10.3390/brainsci12050650
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Comorbidity of Tic Disorders and Obsessive-Compulsive Disorder in Chinese School Students Aged 6–16: A National Survey

Abstract: Background: Obsessive-compulsive disorder (OCD) and tic disorders (TDs) are closely related and considered to etiologically overlap. Both disorders are characterized by repetitive behaviors. TD and OCD often co-occur. The high comorbidity between OCD and TD individuals suggests that we also need to pay more attention to the homogeneity and heterogeneity between TS and OCD. To date, there has been no systematic nationwide epidemiological survey of the mental health (including tic disorders and obsessive-compuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Further differentiating FTLB sufferers from those with tics is that fewer than ¼ of our patients had comorbid OCD, in contrast to tic disorders in which the comorbidity with OCD is estimated at 40–50% (Hirschtritt et al., 2015 ; Termine et al., 2006 ; Yan et al., 2022 ). This discrepancy is consistent with the largest controlled study to date which found that overall a lack of tic‐related OCD behaviors and lack of family history were the strongest predictors of functional tics versus neurodevelopmental tics (Cavanna et al., 2023b ).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Further differentiating FTLB sufferers from those with tics is that fewer than ¼ of our patients had comorbid OCD, in contrast to tic disorders in which the comorbidity with OCD is estimated at 40–50% (Hirschtritt et al., 2015 ; Termine et al., 2006 ; Yan et al., 2022 ). This discrepancy is consistent with the largest controlled study to date which found that overall a lack of tic‐related OCD behaviors and lack of family history were the strongest predictors of functional tics versus neurodevelopmental tics (Cavanna et al., 2023b ).…”
Section: Discussionmentioning
confidence: 80%
“…In our cohort, the percentage of patients with FTLBs and ASD is similar to those with classic tics (9% vs. 7%), though given our small cohort size, this remains to be validated in a larger sample. Data from : Termine C et al., (Termine et al., 2006 ) Yan J et al., (Yan et al., 2022 ) Hirschtritt ME et al., (Hirschtritt et al., 2015 ) Ogundele MO et al., (Ogundele & Ayyash, 2018 ) and Gulisano M, Barone R, Mosa MR, et al. Incidence of Autism Spectrum Disorder in Youths Affected by Gilles de la Tourette Syndrome Based on Data from a Large Single Italian Clinical Cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] TS is estimated to be diagnosed in 0.3% to 0.9% of school-aged children [3] and 0.002% to 0.08% of adults, [4] but there are few adult epidemiological studies worldwide. According to the latest national survey, [5] the latest estimate of TS prevalence in China is 2.46%. TS occurs mostly in men, with a ratio of 4:1, and the symptoms tend to be more severe in men than in women.…”
Section: Introductionmentioning
confidence: 99%
“…Tics are frequently precipitated by unpleasant sensations and urges, with the tic providing relief (1,2). Chronic tic disorders (CTD), a broad category that includes TD, are estimated to affect ~1/50 school aged children in the United States and China (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%